Aerodynamic Performance Improvement by Streamlining The Front Fairing of a Racing Vehicle. Issue 1 (April 2021) - Ferdaus, F; Raghukiran, N; Vijaykumar; Karthikeyan
Abstract: The paper helps to explore and demonstrate the weight reduction of a component with the help of efficient aerodynamics. This can help to reduce fuel consumption and improve the performance of a racing vehicle. The vehicle used is a KTM RC200 2015 which was tested on various factors such as aerodynamics, weight, fuel consumption, and performance. The results were eventually validated with appropriate simulation and experimental trials. To improve and sustain the performance of the engine, it is necessary to explore various factors such as weight reduction through material selection and aerodynamically streamlining the vehicle design. The main component that was tested is the front fairing of the bike. The front fairing plays a very important role in a bike's performance. Therefore, the stock front fairing component is to be replaced with a modified component which also needs to meet all the regulatory safety standards. In the present work, two different front fairing components were used and one of them is made up of plastic representing the stock component while the second one is the customized and improved component made up of glass fiber reinforced epoxy. The results had shown promising improvements to the performance of the vehicle and it was observed that the material density and strength played a factor in the bike's performance and fuel efficiency.